An InGaN/SiNx/Si Uniband Diode Photodetector. Issue 4 (11th January 2022) - Song, Jiaxun; Wang, Xingyu; Xu, Jinyou; Chen, Yongjie; Chen, Hedong; Zhao, Yingzhi; Zhou, Guofu; Nötzel, Richard
Abstract : A novel self‐powered InGaN/SiN x /Si uniband diode photodetector (PD) is introduced. The full band structure is first constructed from the transition of direct tunneling to Fowler‐Nordheim tunneling of holes through the ultrathin SiN x interlayer at forward bias in the dark. Basis is the alignment of the n‐InGaN conduction band with the p‐Si valence band at zero bias. Under illumination, the photocurrent, responsivity, and bandwidth for the self‐powered PD at zero bias indicate two distinct operation modes (i) for longer and (ii) for shorter wavelengths of incident light. The two modes involve (i) absorption in Si and electron tunneling through the SiN x interlayer and (ii) absorption in InGaN and hole transport across the SiN x interlayer. The noise is considerably larger in operation mode (i) than in operation mode (ii). This is attributed to the presence or absence of energy barriers for electron and hole transport in PD operation. Hence, noise is introduced as an independent parameter to discriminate between longer and shorter wavelength regions in dual‐wavelength photodetection. Abstract : A novel InGaN/SiN x /Si uniband diode photodetector is introduced. At longer wavelengths of the incident light, absorption in Si is followed by electron direct tunneling and energy relaxation. At shorter, absorption in InGaN is followed by hole energy relaxation and diffusive transport across the SiN x interlayer. For dual‐wavelength photodetection, noise is introduced as versatile parameter for wavelength discrimination.